2019
DOI: 10.1002/fes3.166
|View full text |Cite
|
Sign up to set email alerts
|

Sowing date and sowing method influence on camelina cultivars grain yield, oil concentration, and biodiesel production

Abstract: Sowing date and sowing method can have a profound influence on the productivity of alternative crops like camelina in semiarid agroecosystems. The objective of this study was to determine the effects of sowing date, sowing method, and cultivar on morphology, phenology, grain yield, oil concentration, oil, and biodiesel production of camelina. A 2‐year study was carried out at the University of Nevada, Reno Main Station Field Laboratory, during the spring to early summer of 2016 and 2017. Treatments were two so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 74 publications
1
14
0
Order By: Relevance
“…Optimization of plant architectural traits through selection can have great potential for increasing biomass and/or seed yield. One of the most crucial plant architecture traits is PH [33]. In the present study, PH showed a positive correlation with all other traits (Table 5).…”
Section: Plant Height (Ph)supporting
confidence: 68%
“…Optimization of plant architectural traits through selection can have great potential for increasing biomass and/or seed yield. One of the most crucial plant architecture traits is PH [33]. In the present study, PH showed a positive correlation with all other traits (Table 5).…”
Section: Plant Height (Ph)supporting
confidence: 68%
“…Persisting stress leads to a continuous decrease in the LRWC during the growth season (Raza et al, 2017). Neupane et al (2019) reported that from the flowering stage onwards, cessation of irrigation led to decreased levels of LRWC in camelina cultivars, but the amount of this decrease was different for each type. In the cultivars exposed to water deficit, LRWC was lower following the cessation of irrigation from the flowering stage onwards, and this value was lower in the cultivars that were sensitive to water deficit.…”
Section: Highlightsmentioning
confidence: 99%
“…Field trials have been conducted in the Western United States to examine the growth and productivity responses of C. sativa, under rain-fed or irrigated conditions, nitrogen (and sulfur) fertilization [21,23,24], sowing date or season [25][26][27][28][29], sowing method [26,28,30], stand reduction by manual plant removal [31], location [24,29,32], and as a fallow replacement crop for winter wheat [12]. Rainfed studies using C. sativa were performed in the Intermountain West [21,[23][24][25]31,33], the Midwest [12,34], and the Pacific Northwest US [24,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Several irrigation studies using C. sativa have also been completed in the Midwest [27,35], Southwest [36], and Western US [37,38]. Two recent studies performed in Nevada reported that C. sativa benefits from early season sowing using a seed drill and adequate fertilization rates [26,39]. However, the performance of multiple varieties under irrigated conditions in this region has not been fully explored.…”
Section: Introductionmentioning
confidence: 99%